2022
DOI: 10.1111/ijac.14240
|View full text |Cite
|
Sign up to set email alerts
|

Advanced ceramics and coatings for erosion‐related applications in mineral and oil and gas production: A technical review

Abstract: The applications of advanced ceramics, composites and coatings in mineral, mining, fuel production, and processing are reviewed. The materials include oxide and non‐oxide ceramics (specifically SiC‐based), ceramic–ceramic, and ceramic–metal composites, coatings on metallic components where functional application properties can be achieved. Some principles of materials selection, specifically for erosion wear and corrosion applications, and manufacturing are considered. The examples of the successful developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 213 publications
0
4
0
Order By: Relevance
“…Wolfe et al [14] highlighted the fact that ceramic coatings provide a durable protective barrier for underlying substrates, surpassing many alternative film barrier materials such as polymers, metals, and glasses in terms of performance and effectiveness. Medvedovski [5] adds that ceramic coatings exhibit superior hardness compared to the particles they encounter during processing, making them a preferred choice for wear applications in comparison to stainless steel protective skin. Additionally, the cracks that may form in ceramic coatings tend to be minimal due to the dominance of fracture toughness and brittleness, factors that contribute significantly to crack propagation and erosion resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Wolfe et al [14] highlighted the fact that ceramic coatings provide a durable protective barrier for underlying substrates, surpassing many alternative film barrier materials such as polymers, metals, and glasses in terms of performance and effectiveness. Medvedovski [5] adds that ceramic coatings exhibit superior hardness compared to the particles they encounter during processing, making them a preferred choice for wear applications in comparison to stainless steel protective skin. Additionally, the cracks that may form in ceramic coatings tend to be minimal due to the dominance of fracture toughness and brittleness, factors that contribute significantly to crack propagation and erosion resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Although the C contents in steels are desired to be lower for enamel production, as mentioned above, the obtained results indicated that the satisfactory enamel surface quality may be attained for different grades of steels significantly expanding technology application. Since the corrosion resistance is basically higher when the ceramic surface has fewer defects and irregularities, which strongly depend on the processing features [37][38][39][40], the proposed routes of the steel surface preparation should promote enamel corrosion resistance.…”
Section: Resultsmentioning
confidence: 99%
“…They are immensely dense, making them identical for applications requiring higher radiation shielding and temperature resistance. 44,45 All the above metal-based micro-particles can enhance composite materials' physical, mechanical, and thermal characteristics, along with incremented impact resistance. The novelty of this investigation presents a significant development in the sector of polymer composites, as it studies the influences of tungsten, nickel, and ferrous microparticles as reinforcement in glass fabric reinforced polyester and vinyl-ester hybrid composites.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the tungsten micro‐particles possess higher melting points. They are immensely dense, making them identical for applications requiring higher radiation shielding and temperature resistance 44,45 . All the above metal‐based micro‐particles can enhance composite materials' physical, mechanical, and thermal characteristics, along with incremented impact resistance.…”
Section: Introductionmentioning
confidence: 99%